La investigación diacrónica sobre el español de Canarias: una visión historiográfica - Medina López, Javier (Pontificia Universidad Católica del Perú, 2023)
This article presents the development of research on the history of the Spanish language in the Canary Islands from a dialectal and historiographical perspective. We have considered both the contributions that conceive the current state of Canarian speech as an uninterrupted historical process, as well as those that rely on a methodology based on the transcription of historical documents. The latter are mainly part of the “Project for the Historical Study of Spanish in America”, carried out by the Asociación de Lingüística y Filología de América Latina (ALFAL) since 1993. In both cases, the bibliographical relationship will serve as the status quaestionis in this field of Canarian research. Today we have an extensive bibliographic panorama that shows how Canarian Spanish has evolved historically in the context of the Castilian expansion towards the Atlantic since the beginning of the 15th century.

Este artículo muestra el desarrollo de la investigación sobre la historia del español en Canarias desde una perspectiva dialectal e historiográfica. Se consideran tanto las aportaciones que conciben el estado actual de las hablas canarias como un proceso histórico ininterrumpido, como aquellas que parten de una metodología basada en la transcripción de documentos históricos. Esta segunda fase se enmarca, principalmente, en el “Proyecto del Estudio Histórico del Español de América”, dentro del marco de la Asociación de Lingüística y Filología de América Latina (ALFAL), desde 1993. En ambos casos, la relación bibliográfica servirá de status quaestionis en esta parcela de la investigación canaria. Hoy contamos con un amplio panorama bibliográfico que muestra cómo ha sido el español canario en su evolución histórica en el marco de la expansión castellana hacia el Atlántico desde comienzos del siglo XV.
Diachronic Research on the Spanish of the Canary Islands: A Historiographical Vision
Keywords: History; Of Spanish in the Canary Islands; Linguistic historiography; Spanish language; Atlantic Spanish; Historia del español en Canarias; Historiografía lingüística; Lengua española; Español atlántico; https://purl.org/pe-repo/ocde/ford#6.02.06